1981
DOI: 10.1002/ijc.2910280508
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 125I‐labelled human αinterferon to human lymphoid cells

Abstract: To investigate the binding of interferon to human lymphoid cells, we purified human alpha interferon and radio-labelled it with iodine-125. Binding at 4 degrees C could be saturated and was inhibited by unlabelled interferon; it was specific for cells of human origin. Dissociation constants for the complex of interferon and receptor site were of the order 10(-9)-10(-11) M. All human cells tested showed such binding. Occupation of these high-affinity sites, at 37 degrees C, was compared with the inhibition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 33 publications
5
47
0
Order By: Relevance
“…The interferon preparations used were the same as those described in the previous article. Purification and radiolabelling of human interferon-~ from Namalwa cells were carried out as described by Mogensen et al (1981). 3zsI-IFN-c~ had a titre of 16000 international units/ml and a radioactive content of 75 [tCi/~tg IFN protein at the time of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The interferon preparations used were the same as those described in the previous article. Purification and radiolabelling of human interferon-~ from Namalwa cells were carried out as described by Mogensen et al (1981). 3zsI-IFN-c~ had a titre of 16000 international units/ml and a radioactive content of 75 [tCi/~tg IFN protein at the time of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneously occurring interferon-resistant Burkitt's lymphoma-derived cell lines such as Raji or Namalwa also retain a similar partial interferon sensitivity (Adams et al, 1975). These cells (Mogensen et al, 1981) in common with clones DIFz and DIF3 possess functional interferon receptors (Tovey et al, 1983), suggesting that the mechanism determining interferon resistance is initiated after binding of interferon to its receptor. It is interesting to note that to date the only interferon-resistant cells that have been described, which are completely refractory to all the effects of interferon tested, are mouse L1210 R cells which lack a functional receptor for interferons-ct and -fl (Aguet, 1980;Aguet & Blanchard, 1981), and human HEC-1 cells (Chen et al, 1981) which have also been shown to exhibit reduced binding of interferons-~ and -fl (Verhaegen-Lewalle et al, 1982).…”
Section: Dron and M G Toveymentioning
confidence: 99%
“…Binding experiments were carried out as described previously (Mogensen et al, 1981). Briefly, exponentially growing cells were incubated for the times indicated with different concentrations of ~ 25I-labelled IFN-~2 at either 4 or 37 °C and then immediately placed in ice.…”
Section: -6770 © 1986 Sgmmentioning
confidence: 99%
“…4, 5). DISCUSSION Cells have been described for which the phenotype of IFN resistance has been shown to be due to a lack of functional IFN receptors (Aguet & Blanchard, 1981); other cells have been characterized which are resistant to certain actions of IFN even though they possess IFN receptors (Affabris et al, 1983;Fuse et al, 1984;Aguet et al, 1981 ;Mogensen et al, 1981). The binding of IFN to its cell surface receptor is, however, a complex process which may involve an activation step (Mogensen & Bandu, 1983;.…”
Section: Analysis Of the Binding Of125i-ifn-~2 To Daudi And Die8 Cellsmentioning
confidence: 99%